Adverse Childhood Experiences and Psychological Correlates in College Students: A Comparison of Student-Athletes and Non-Student-Athletes - Matthew D. Powless; Zachary A. Pilot; Elisabeth R. Brown; Mikaila C. Ealum; Kaitlyn N. Back; Sabrina Yamashita; Kaitlin Mindiola (Sports)
Over the last two and a half decades, there has been a surge of research into adverse childhood experiences (ACEs). ACEs have been found to be a significant predictor of mental health outcomes in adulthood, and researchers have begun to explore the relationship between ACEs and mental health outcomes in athletes. However, to the best of the authors’ knowledge, no study has directly compared the mental health of student-athletes to non-student-athletes in the context of exposure to ACEs. In the present study, we compared psychological outcomes observed in college students (123 student-athletes and 149 non-student-athletes) on two mental health variables—depressive symptoms and difficulties in emotion regulation—at one university in the U.S. Results indicated that exposure to ACEs had a significant effect on both depressive symptoms and difficulties in emotion regulation, while student-athlete status only had a significant effect on depressive symptoms. There was no significant interaction effect between exposure to ACEs and student-athlete status. This pattern of main effects and an absence of an interaction effect remained even when the psychological trait of hardiness was controlled for. The implications and limitations of these results will be discussed.